Scoop: Decentralized and Opportunistic Multicasting of Information Streams - Gunawardena, Dinan; Karagiannis, Thomas; Proutiere, Alexandre; Santos-Neto, Elizeu; Vojnovic, Milan (2010)
This work considers the problem of delivering information streams to interested mobile users that leverages both access to the infrastructure and device-to-device data transfers. The goal is to design practical relaying algorithms that aim at optimizing a global system objective that accounts for two important aspects: first, the user interest in content with respect to its type and delivery time; and, second, resource constraints such as storage and transmission costs. We first provide evidence that extending the information dissemination from one to two hops leads to significant performance gains on deliverying content to users, in practice. More specifically, paths that are longer than two hops lead to diminishing benefits. We also show that correlation of delay through paths is typically significant, thus asking for system design that would allow for general user mobility. We propose a class of relaying strategies (referred to as SCOOP) that aim at optimizing a global system objective, are fully decentralized, require only locally observed states by individual devices, and allow for general user mobility. These properties characterize a practical scheme whose efficiency is demonstrated using real-world mobility traces.